Targeting NADPH oxidase with a novel dual Nox1/Nox4 inhibitor attenuates renal pathology in type 1 diabetes - Gorin, Yves (Am J Physiol Renal Physiol, 2015)
Reactive oxygen species (ROS) generated by Nox NADPH oxidases may play a critical role in the pathogenesis of diabetic nephropathy (DN). The efficacy of the Nox1/Nox4 inhibitor GKT137831 on the manifestations of DN was studied in OVE26 mice, a model of type 1 diabetes. Starting at 4–5 mo of age, OVE26 mice were treated with GKT137831 at 10 or 40 mg/kg, once-a-day for 4 wk. At both doses, GKT137831 inhibited NADPH oxidase activity, superoxide generation, and hydrogen peroxide production in the renal cortex from diabetic mice without affecting Nox1 or Nox4 protein expression. The increased expression of fibronectin and type IV collagen was reduced in the renal cortex, including glomeruli, of diabetic mice treated with GKT137831. GKT137831 significantly reduced glomerular hypertrophy, mesangial matrix expansion, urinary albumin excretion, and podocyte loss in OVE26 mice. GKT137831 also attenuated macrophage infiltration in glomeruli and tubulointerstitium. Collectively, our data indicate that pharmacological inhibition of Nox1/4 affords broad renoprotection in mice with preexisting diabetes and established kidney disease. This study validates the relevance of targeting Nox4 and identifies GKT137831 as a promising compound for the treatment of DN in type 1 diabetes.